Application of Continuous Data Assimilation in High-Resolution Ocean Modeling (Communications in Computational Physics, 2024)
We demonstrate a formulation of the Azouani-Olson-Titi (AOT) algorithmin the MPAS-Ocean implementation of the primitive equations of the ocean, presentingglobal ocean simulations with realistic coastlines and bathymetry. We observe an exponentially fast decay in the error before reaching a certain error level, which dependson the terms involved and whether the AOT feedback control term was handled implicitly or explicitly. A wide range of errors was observed for both schemes, with theimplicit scheme typically exhibiting lower error levels, depending on the specific physical terms included in the model. Several factors seem to be contributing to this widerange, but the vertical mixing term is demonstrated to be an especially problematicterm. This study provides insight into the promises and challenges of adapting theAOT algorithm to the setting of high-resolution, realistic ocean models.
Keywords: Continuous data assimilation; Azouani-Olson-Titi; oceanography; MPAS-Ocean; primitive equations; nudging.